Heterogeneity in the evaluation of suspected MIS-C: a cross-sectional vignette-based survey - Claudia A. Rosu; Anna M. Martens; Jeffrey Sumner; Eva J. Farkas; Puneeta Arya; Alexy Boudreau Arauz; Vandana L. Madhavan; Hector Chavez; Shawn D. Larson; Oluwakemi Badaki-Makun; Daniel Irimia; Lael M. Yonker (BMC, 2022)
Abstract Background and Objectives Multisystem Inflammatory Syndrome in Children (MIS-C) is an emerging complication of COVID-19 which lacks a definitive diagnostic test and evidence-based guidelines for workup. We sought to assess practitioners' preferences when initiating a workup for pediatric patients presenting with symptoms concerning for MIS-C. Methods In a cross-sectional vignette-based survey, providers were presented with clinical vignettes of a patient presenting with 24 h of fever from a community with high rates of COVID-19. Respondents were asked about their general practices in pursuing a workup for potential MIS-C including testing obtained, criteria for diagnosis, and timing to confirm or rule out the diagnosis. Results Most of the 174 respondents were physicians from the United States at academic medical centers. The majority of providers would not initiate MIS-C workup for fever and non-specific symptoms unless the fever lasted more than 72 h. Skin rash, abdominal pain, and shortness of breath were symptoms that raised greatest concern for MIS-C. Most providers would obtain COVID-19 PCR or antigen testing, plus blood work, in the initial workup. The list of laboratory studies providers would obtain is extensive. Providers primarily rely on cardiac involvement to confirm a MIS-C diagnosis, and establishing a diagnosis takes 24-48 h. Conclusions Significant heterogeneity exists amongst providers as to when to initiate the MIS-C workup, the order and content of the workup, and how to definitively diagnose MIS-C. A diagnostic test with high sensitivity and specificity for MIS-C and refined evidence-based guidelines are needed to expedite diagnosis and treatment.